1999
DOI: 10.1111/j.1469-7793.1999.639ad.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a functional Kir4 family inward rectifier K+ channel from a gene cloned from mouse liver

Abstract: A low stringency polymerase chain reaction (PCR) homology screening procedure was used to probe a mouse liver cDNA library to identify novel inward rectifier K+ channel genes. A single gene (mLV1) was identified that exhibited extensive sequence homology with previously cloned inward rectifier K+ channel genes. The mLV1 gene showed greatest sequence identity with genes belonging to the Kir4 subfamily. The amino acid sequence of mLV1 was 96 % identical to a Kir channel cloned from human kidney (hKir4.2), and ≈6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(100 citation statements)
references
References 43 publications
4
96
0
Order By: Relevance
“…Our studies identify the involvement of one Kir channel subunit, Kir4.2, downstream of the ␣9 integrin in a pathway that enhances cell migration. Kir4.2 is present in a wide variety of tissues, including lung and liver, that are also sites of expression of the ␣9 integrin subunit (48,49). Thus, it remains plausible that these proteins functionally cooperate in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies identify the involvement of one Kir channel subunit, Kir4.2, downstream of the ␣9 integrin in a pathway that enhances cell migration. Kir4.2 is present in a wide variety of tissues, including lung and liver, that are also sites of expression of the ␣9 integrin subunit (48,49). Thus, it remains plausible that these proteins functionally cooperate in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…3f). Kir4.2, which has been reported to have a molecular mass of ~35 kDa to 40 kDa (Ferrando-Miguel et al, 2004;Hill et al, 2002), possesses a glycosylation motif (Pearson et al, 1999;Shuck et al, 1997). Thus, the two bands in brain and retina may represent unglycosylated and glycosylated dimers (Hibino et al, 2004).…”
Section: Expression Of Kir Proteins In Native Human Rpe and Neural Rementioning
confidence: 99%
“…Kir4.2 subunits form K + channels with intermediate inward rectification and can co-assemble with Kir5.1 subunits, which influence its rectification and gating properties (Pearson et al, 1999). Unlike Kir4.1 channels, Kir4.2 channels expressed in mammalian cells are insensitive to intracellular pH within the physiological range (Lam et al, 2006).…”
Section: Physiological Significancementioning
confidence: 99%
“…Block by external Cs ϩ was highly voltage sensitive, and required Ͼ20 mM at Ϫ80 mV. No other studies have been reported for human Kir4.2, but in mouse Kir4.2, Cs ϩ blocks in the 100 M (ϳϪ120 mV) range (13). Kir channels display a broad range of sensitivities to Cs ϩ block, with K d values ranging over a 100-fold range near resting membrane potentials.…”
Section: Probing Kir With Blockers and Activatorsmentioning
confidence: 99%
“…Kir channels display a broad range of sensitivities to Cs ϩ block, with K d values ranging over a 100-fold range near resting membrane potentials. Kir channels with micromolar sensitivity to external Cs ϩ include hKir2.1 at Ϫ92 mV (28), hamKir2.1 at ϳϪ80 mV (29), mKir3.2 at ϳϪ90 mV (30), rat Kir4.1 at ϳϪ75 mV (31), and mKir4.2 at ϳϪ120 mV (13). Kir channels with millimolar sensitivity to Cs ϩ block include Kir1.1 at Ϫ80 mV (32), Kir2.1 at ϳϪ110 mV (17), Kir2.4 at ϳϪ80 mV (33), and hKir7.1 at ϳϪ60 mV (34).…”
Section: Probing Kir With Blockers and Activatorsmentioning
confidence: 99%